TANGGUNG JAWAB GEREJA TERHADAP PERSOALAN LINGKUNGAN DI JEMAAT GMIM SYALOM TUMINTING MELALUI STRATEGI PASTORAL KONSELING - Samuel Wailan Leonard Wanget; Meily Meiny Wagiu; Jekson Berdame; Melkisedek Teleng (POIMEN Jurnal Pastoral Konseling, 2024)
This research aims to explore the role of the church in environmental conservation and identify pastoral strategies that can be implemented to enhance the awareness and participation of congregants in ecological responsibility. Through a case study at GMIM Syalom Tuminting Church, this study reveals the importance of developing church programs focused on environmental preservation and the necessity of involving all congregants in supporting and executing these programs. Active participation of congregants in environmental stewardship, both through church programs and personal initiatives, is identified as a key element in caring for creation as part of spiritual responsibility. The research also underscores the importance of ongoing research and educational activities to increase the understanding and awareness of congregants about the significance of environmental responsibility. The findings of this study are expected to serve as a reference for other churches in developing effective pastoral strategies for environmental conservation and inspiring congregants to engage in sustainable ecological efforts.